Estándar de usabilidad para la interfaz gráfica de usuario en los proyectos de desarrollo de software. - Carrión Chamba, Rober Alonso (2014)
The title work represents the gather information about the use of software that helps in the creation of standard for user's graphic interface in software project development. The information was gathering of doctors’ thesis, masters’ thesis, degree’s thesis, scientific articles and official Web pages of Web organisms that regulate the Web contained. The constructions of standard of use begins with the analysis of officials sites and the best universities in the world, universities of Ecuador, government Webs of Ecuador and social nets with the purpose of liberating three more accessible sites in each group and get results, proceeded to recognize common characteristic in the interface of the user in the selected. After of have getting the common characters in the interface of Web sites proceeds to analysis the world wide Web consortium request about the access to the Web and the ISO 9241-11 request about the use of software to give a list of characters of use in each Web site group. After validate the characteristics’ use of the Web sites with the standards of use that is a group of rulers and advices that help to developers and designers of graphic interface in the development of intuitive and useful interface for the user in the development of their activities, with the use of standards building you proceeded to make the use standard for the graphic interface in the development of interfaces intuitive-ace and useful to the user in the development of interfaces intuitive-ace and useful to the user in the development of their activities. With the standard of made use you proceeded to carry out an insole webs through technologies HTML5 and CSS3 webs that serve as opening for construction with a high level of usability.